WARISAN BUDAYA KOPI SEKANAK KEPULAUAN RIAU - Yayan Mardianah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2021)
This article discusses about Kopi Sekanak tradition. This research is a qualitative research with oral history method. Data collected through interviews and literature study. The result shows that Kopi Sekanak is the heritage from Melayu royal government in the past. There are local wisdom in Kopi Sekanak which is described in this article. Kopi Sekanak also include in intangible cultural heritage category.